Comparative Study of Sales Contracts in Law - Mariana, Mariana; Amri, Amsanul; Kheriah, Kheriah; Izwany, Bonita; Kamaliah, Nurul (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the differences between Islamic Law (Sharia) and Civil Law in the application of sales contracts, as well as the practical implementation of both legal systems in daily transactions. Islamic Law emphasizes moral and ethical aspects by ensuring transactions are free from prohibited elements such as riba, gharar, and maysir, while Civil Law focuses more on legality and the freedom of contract. This research employs a descriptive qualitative method with a normative juridical approach, examining legal provisions and the practice of sales contracts based on data from primary, secondary, and tertiary sources. The findings show that the rules and conditions of sales contracts in Islamic Law are stricter, prioritizing compliance with Islamic principles, while Civil Law is more flexible in agreements between parties. The application of contracts such as murabaha, salam, and istisna in Islamic finance institutions reflects a commitment to moral principles, whereas sales contracts in Civil Law are more common in markets and commercial activities. This study provides recommendations for harmonizing both legal systems to create transactions that are fair and in accordance with the social values upheld by society.